Maturational advantage of early maturers in youth sport - Ostojic, S. M. (Medicina dello Sport, 2017)
BACKGROUND: Early maturers dominate in youth sport, yet the degree of maturational advantage against normal and late maturers is poorly described. METHODS: In a sample of 167 athletic boys and adolescents (age 6.9-18.5 years) we assessed biological age (BA) using Greulich-Pyle skeletal age estimation method, and compared biological to chronological age (CA) for each participant. Participants` maturation status was determined according to following criteria: early maturers (BA>CA by 6 months or more); normal maturers (BA above or below CA by =6 months); and late maturers (BA retarded by more than 6 months to CA). RESULTS: Among boys in our cohort, 36.5% were categorized as early maturers, 46.7% as normal maturers, and 16.8% were classified as late maturers (P=0.002), while an average maturational advantage of early maturers vs. late maturers was 1.8 years. CONCLUSIONS: It seems that normal and early maturers predominate in youth sport, with athletic boys and adolescents displayed an advanced biological age.